THE MECHANICAL ANALYSIS OF PIPELINE LIFTING DURING THE HORIZONTAL DIRECTIONAL CROSSING - DONG ZongZheng; FU BiWei; XI YanQing; LIU Xu (Jixie qiangdu)
If the hoisting position is bad during the engineering application of the lifting pipe,which may bring the serious influence when the pipe smoothly enters the grave,even happen stuck pipe and tube flat accidents. Through the mechanical analysis of the pipe lifting,themathematical model about lifting point position and the grave angle was established,which on the basis of reasonable assumptions. The location of the lifting point 2 affects on the size of the grave angle more than lifting point 1by mathematical model analysis. And then compared with the calculated value of mathematical model and the value of test measurement,the relative error of theoretical calculation value and experimental value that is about 5. 8% was discovered.Therefore,the mathematical model can be used to guide the actual construction.